Keberlanjutan Modern: Workshop E WORKSHOP ECOPRINT SEBAGAI BENTUK SENI BERKELANJUTAN DI ERA MODERN MENEKANKAN ASPEK RAMAH LINGKUNGAN: Pendahuluan - Difitri, Tria; Hayati, Riza Sativana (LPPM Universitas Al Muslim, 2025)
Economic dependence on the agricultural sector, suboptimal utilization of village natural potential, and minimal community skills in processing local resources are the main problems identified in Dusun Kampung Baru. This condition is exacerbated by limited access to creative economic opportunities that support improving family welfare. Therefore, an innovative approach is needed that not only provides economic solutions but also considers aspects of environmental sustainability. The ecoprint workshop in Ajakkang Village, Dusun Kampung Baru is a community empowerment initiative that combines aspects of the creative economy with environmental conservation. This community service activity was carried out in three main stages, namely team coordination, coordination with the village government, and implementation of the workshop including socialization and technical training. This activity was attended by 15 PKK members, and the workshop successfully introduced natural dyeing techniques to textiles with local organic materials. Participants were trained by KKN students starting from the material preparation stage, the mordanting process, to finishing the product in the form of a tote bag. The results of this activity showed a high level of enthusiasm from the participants and the success of making products with unique motifs. This program not only provides new skills, but opens up opportunities for the development of an environmentally friendly creative economy in Ajakkang Village.